EMPLOYER BRANDING OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) IN INDONESIA - Purusottama, Ambara; Trilaksono, Teddy; Ardianto, Ari (Economic Faculty, Attahiriyah Islamic University, 2019)
This study attempts to narrow the gaps that exist in the literature about branding in the context of micro, small and medium enterprises (MSMEs). The research method used is a qualitative approach through in-depth interviews with Owners, Managing Directors, and Human Resource Managers in MSMEs. The results of this study indicate that the UMKM employer branding is still limited to intention. It can be seen from the absence of programs or activities that support employer branding programs that are felt directly by their employees. This is induced by the focus of MSME businessmen who are still on fundamental issues such as financial constraints and the absence of loyal consumers. The results of this study can be used by educators or stakeholders in Indonesian MSMEs as a reference for formulating employer branding approaches and strategies that are in line with the characteristics of MSMEs in Indonesia. Keywords: Employer branding, Human resources management, Micro, small and medium enterprises